(untitled) (Issues in Social and Environmental Accounting (ISEA), 2010)
When one considers that all profits are not made equally, philosophy, history, anthropology become pre-requisites for professional accounting and finance graduates. This allows for a complete understanding of an intimately related financial market that exerts tremendous influ ence on socio-economic conditions. A graduate from a liberal arts institution may be worth more than what his or her academic balance sheet shows. A liberal arts education teaches one how to think, how to analyze, how to read, how to write, how to develop a persuasive argu ment. Any liberal arts education, even vaguely defined becomes an intellectual antidote to the overwhelming flood of information and technological change. A liberal arts education teaches students to read and to reason; to learn something about the range of human expression; to con sider the great literature and ideas of world civilizations; to recognize and construct arguments; and to have sensitivity towards others’ thinking. It also makes possible a genuine kind of citi zenship without which democracy and markets crumble. This study presents emerging trends in accounting as a growing discipline in liberal arts institutions whose mission is aligned with social goals.